A method for the assessment of the internal structure of bio-aggregate concretes. (30th July 2016) - Williams, Joseph; Lawrence, Mike; Walker, Pete
Highlights: A novel method for assessing bio-aggregate composites is proposed. 2D and 3D image analysis used to assess aggregate orientation. Specimens of hemp-lime found to have a strong anisotropic internal structure. Abstract: The thermal and mechanical properties of bio-aggregate concretes are known to be anisotropic. This is assumed to be the result of an orientated internal arrangement of particles; the internal structure of other aggregate composite materials is known to be a determiner of physical properties and has been the focus of much study. Despite this the internal structure of bio-aggregate concretes has to date only been considered qualitatively. This work presents a novel method for the assessment of the internal structure of bio-aggregate concretes through the application of image analysis. Results are presented for the assessment of hemp-lime specimens and demonstrate a significant anisotropy within the material. These results account for anisotropic thermal and mechanical behaviour observed elsewhere and demonstrate the importance of the internal structure in determining the properties of these materials. This innovative technique represents a significant breakthrough in the search for optimisation of the performance of renewable, low carbon insulation materials. This class of materials is critical to the sustainable future of the construction industry.